The Bible in African American Perspectives - Bellis, Alice Ogden (Teaching theology and religion, 1998)
This modified “note from the classroom” is a dialogue between two scholars about African American study of the Bible. Bellis introduces the subject by advocating the primacy of social location and the African American student's religious experience in the method that she uses in her classes. (Her sample bibliography, syllabus and course outline for teaching about the Bible in African American perspectives can be found on the Wabash Center web page: http://www.wabashcenter.wabash.edu.) Brown's response takes a different stance with regard to the relative importance for exegesis of historical-critical method and the reader's social location. While Bellis and Brown agree on the appeal that the King James Version holds for many African Americans (but for different reasons), their differing assessments of translations, the distinctiveness of African American interpretations, and the ethnicity of Biblical characters models a lively discussion of issues in teaching and learning.